EVALUASI KOMPETENSI GURU DALAM PEMBELAJARAN ABAD 21: ANALISIS PROSES MODEL CIPP DI SMPI-PK MUHAMMADIYAH DELANGGU - Afifah, Khoiri Yahya; Zaenal Abidin; Ahmad Muhibbin; Agus Susilo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to evaluate the implementation of teacher competency in 21st- century learning at SMP IPK Muhammadiyah Delanggu, specifically highlighting the quality of the teaching and learning process execution. This evaluation research utilizes the CIPP Model (Context, Input, Process, Product) approach, with the main focus on the Process dimension to analyze how teacher competencies are translated into classroom instruction. Data were collected through structured observation of core subject teachers, in-depth interviews with teachers and school management, and analysis of Lesson Implementation Plans (RPP/Lesson Plans). The results of the process analysis indicate that the implementation of Collaboration, Communication, and Innovation competencies falls into the Fairly Good category, supported by ICT integration and the commitment of the school management. Teachers consistently facilitate group assignments and utilize simple digital media. Furthermore, the integration of Islamic values in general subjects was also well-executed, aligning with the institution's vision. However, key findings identify a significant gap in Critical Thinking competency. The average proficiency of teachers in triggering Higher Order Thinking Skills (HOTS) questions remains relatively low, indicating insufficient transfer from training to classroom practice. The main obstacle identified was the lack of duration and intensity of practical mentorship following training (clinical supervision). This study recommends the need for continuous professional development more focused on strengthening critical pedagogy, particularly in designing stimuli to enhance students' analytical thinking skills.